2019
DOI: 10.1016/j.jenvman.2018.09.079
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and mechanisms of cadmium adsorption onto biogenic aragonite shells-derived biosorbent: Batch and column studies

Abstract: Calcium carbonate (CaCO 3)-enriched biomaterial derived from freshwater mussel shells (FMS) was used as a non-porous biosorbent to explore the characteristics and mechanisms of cadmium adsorption in aqueous solution. The adsorption mechanism was proposed by comparing the FMS properties before and after adsorption alongside various adsorption studies. The FMS biosorbent was characterized using nitrogen adsorption/desorption isotherm, X-ray diffraction, scanning electron microscopy with energy dispersive spectro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 80 publications
(27 citation statements)
references
References 43 publications
2
23
0
Order By: Relevance
“…e rod-shaped FSS particles had many crystalline microlayers and their thickness and width, respectively, were 1.5 μm and 2.8 μm. is result agreed with several previous reports by Van et al [21] with S BET of 1.45 m 2 /g for a CaCO 3 -rich biosorbent-biogenic aragonite shells-and 2.09 m 2 /g for golden apple snail shells [22]. In addition, the characteristic peaks of calcium silicate (Ca 2 SiO 4 ) were also observed with low intensity on the XRD pattern, indicating the small amount of this compound present in FSS.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…e rod-shaped FSS particles had many crystalline microlayers and their thickness and width, respectively, were 1.5 μm and 2.8 μm. is result agreed with several previous reports by Van et al [21] with S BET of 1.45 m 2 /g for a CaCO 3 -rich biosorbent-biogenic aragonite shells-and 2.09 m 2 /g for golden apple snail shells [22]. In addition, the characteristic peaks of calcium silicate (Ca 2 SiO 4 ) were also observed with low intensity on the XRD pattern, indicating the small amount of this compound present in FSS.…”
Section: Resultssupporting
confidence: 93%
“…us, these biomaterials are used to develop CaCO 3 -rich materials for preparing low-cost adsorbents. For instance, Flores-Cano et al [19] developed an eggshell-derived biosorbent for Cd adsorption; El Haddad [20] used a calcined mussel shell (62.24% CaCO 3 )-derived biosorbent to remove Basic Fuchsin dye; Van et al [21] developed a green biosorbent derived from freshwater mussel shells (contain >90% CaCO 3 ) for the removal of Cd with an adsorption capacity of 26.6 mg/g.…”
Section: Introductionmentioning
confidence: 99%
“…Different adsorbents such as waste adsorbents are becoming popular for waste management and creating a sustainable world. The most commonly used waste adsorbents are waste bivalve shells [27,28]. Currently, waste eggshell is also well used for the treatment of wastewater [6,17,29,30].…”
Section: Introductionmentioning
confidence: 99%
“…The normalised XRPD patterns show the presence of both an amorphous phase, which is associated with the organic component of the material, e.g. chitin/chitosan polymer and a crystalline phase, which was identified as calcite (Swanson et al 1953;Zhou et al 2016;Cai et al 2019). The broad diffraction peaks observed at around 9.6°and 19°in the raw material (representing the amorphous chitin structure) are found to sharpen after activation, suggesting the material has crystallised during the activation process (Arulvel et al 2017).…”
Section: Xrpdmentioning
confidence: 99%
“…Hence, increasing IR made the deacetylation process more efficient, aiding enhanced development of chitosan on both the exterior and interior surface of the CCM (Chu 2002). KOH also increases the pH pzc at which the surface of the adsorbent is electroneutral (pH pzc = 8.78), and it has been reported that the pH pzc of similar calcium-chitin-based adsorbents are in the range of 9-11.4 (Tap Van et al 2018). Theoretically, below this value, the surface of the material in solution is positively charged.…”
Section: Modification and Optimisation Processmentioning
confidence: 99%